MiR-324-5p inhibition after intrahippocampal kainic acid-induced status epilepticus does not prevent epileptogenesis in mice - McGann, Amanda M.; Westerkamp, Grace C.; Chalasani, Alisha; Danzer, Cole S. K.; Parkins, Emma V.; Rajathi, Valerine; Horn, Paul S.; Pedapati, Ernest V.; Tiwari, Durgesh; Danzer, Steve C.; Gross, Christina (Frontiers in Neurology, 2023)
Background Acquired epilepsies are caused by an initial brain insult that is followed by epileptogenesis and finally the development of spontaneous recurrent seizures. The mechanisms underlying epileptogenesis are not fully understood. MicroRNAs regulate mRNA translation and stability and are frequently implicated in epilepsy. For example, antagonism of a specific microRNA, miR-324-5p, before brain insult and in a model of chronic epilepsy decreases seizure susceptibility and frequency, respectively. Here, we tested whether antagonism of miR-324-5p during epileptogenesis inhibits the development of epilepsy. Methods We used the intrahippocampal kainic acid (IHpKa) model to initiate epileptogenesis in male wild type C57BL/6 J mice aged 6–8 weeks. Twenty-four hours after IHpKa, we administered a miR-324-5p or scrambled control antagomir intracerebroventricularly and implanted cortical surface electrodes for EEG monitoring. EEG data was collected for 28 days and analyzed for seizure frequency and duration, interictal spike activity, and EEG power. Brains were collected for histological analysis. Results Histological analysis of brain tissue showed that IHpKa caused characteristic hippocampal damage in most mice regardless of treatment. Antagomir treatment did not affect latency to, frequency, or duration of spontaneous recurrent seizures or interictal spike activity but did alter the temporal development of frequency band-specific EEG power. Conclusion These results suggest that miR-324-5p inhibition during epileptogenesis induced by status epilepticus does not convey anti-epileptogenic effects despite having subtle effects on EEG frequency bands. Our results highlight the importance of timing of intervention across epilepsy development and suggest that miR-324-5p may act primarily as a proconvulsant rather than a pro-epileptogenic regulator.